Histological studies of powdery mildew (Erysiphe graminis f. sp. tritici) resistance in wheat (Triticum aestivum) - BASANDRAI*, A.K.; PAUL, R.; GULATI, A.; TYAGI, P. D.; BASANDRAI, DAISY (Indian Phytopathology, 2011)
Infection process of Erysiphe graminis f. sp. tritici pathotype 4 was examined on primary seedling leaves of eightÂ wheat genotypes having specific gene(s) for powdery mildew resistance and two commercially grown cvs., in comparison withuniversal susceptible cv. Agra Local. In incompatible host parasite interactions, conidial germination and appressoriurnformation were less, particularly in Norka x Cc8 (Pm 1). Germtubes appeared weak, shrivelled and distorted in Sappo (Pm 2+4b)Â and Kronjuwel (Pm 4b+8). Haustorial abortion, less secondary haustoriurn production, and restricted growth of mycelial wefts,Â with no subsequent conidiophore formation were observed in TP 114 (Pm 2+6). In Norka x Cc8, Sappo and Kronjuwel, developmentÂ of haustoriurn and elongated secondary hypha was completely absent. In compatible host parasite combinations, the sequenceÂ of infection events was similar to the susceptible check, differences were observed in components of rate reducing resistance.Â Incubation period and latent period were longer in Amigo (Pm 17), HS 240 and HS 295. In CS/Hope (pm 5), Kavkaz (Pm 8), Amigo,Â and HS 295 colony size and number per unit area and sporulation index were reduced, whereas in Transec (Pm 7) colony sizeÂ and in HS 240 sporulation index were at par with the susceptible check. Sporulation capacity was also reduced in all theÂ genotypes.